1992
DOI: 10.1021/tx00027a006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of the pyridoindole stobadine. Pulse radiolytic characterization of one-electron-oxidized stobadine and quenching of singlet molecular oxygen

Abstract: Antioxidant properties of stobadine, a pyridoindole derivative described to exhibit cardioprotective properties, were characterized. The radical scavenging potential of stobadine was evaluated using pulse radiolysis with optical detection, by which it is shown that one-electron oxidation of stobadine with radicals such as C6H5O., CCl3O2., Br2.-, and HO. (reaction rate constants approximately 5 x 10(8)-10(10) M-1 s-1) leads to the radical cation (absorbance maxima at 280 and 445 nm) which deprotonates from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…1B). It was demonstrated that one-electron oxidation of stobadine leads to the formation of its radical cation (Steenken et al, 1992). That deprotonates from the indolic nitrogen and gives a resonance stabilised nitrogen-centred radical.…”
Section: Redox Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…1B). It was demonstrated that one-electron oxidation of stobadine leads to the formation of its radical cation (Steenken et al, 1992). That deprotonates from the indolic nitrogen and gives a resonance stabilised nitrogen-centred radical.…”
Section: Redox Propertiesmentioning
confidence: 99%
“…< 5x10 6 6.6 x 10 8 (Steenken et al, 1992) 2.5 x 10 6 3.7 x 10 8 (Simic, 1980;Davies et al, 1988) DPPH . 4.9 x 10 2 (Rackova et al, 2004) 1.6 x 10 3 (Rackova et al, 2004) C 6 H 6 O .…”
Section: Stobadine Troloxmentioning
confidence: 99%
See 3 more Smart Citations